Activity/rest rhythm of depressed adolescents undergoing therapy: case studies - Maria Eugênia Mesquita (Trends in Psychiatry and Psychotherapy)
Abstract Introduction: Disorders of circadian rhythms have been reported in studies of both depressed children and of depressed adolescents. The aim of this study was to evaluate whether there is a relationship between the 24-hour spectral power (24h SP) of the activity/rest rhythm and the clinical course of depression in adolescents. Methods: Six 14 to 17-year-old adolescents were recruited for the study. They were all suffering from major depressive disorder, according to the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) criteria, as identified by the Schedule for Affective Disorders and Schizophrenia for School Aged Children: Present and Lifetime Version (K-SADS-PL). Depressive symptoms were assessed using the Children's Depression Rating Scale - Revised (CDRS-R) and clinical evaluations. Locomotor activity was monitored over a period of 13 consecutive weeks. Activity was measured for 10-minute periods using wrist-worn activity monitors. All patients were prescribed sertraline from after the first week up until the end of the study. Results: We found a relationship between high CDRS values and low 24-hour spectral power. Conclusions: The 24h SP of the activity/rest rhythm correlated significantly (negatively) with the clinical ratings of depression.